Processing of plant fiber composites by liquid molding techniques: an overview - Francucci, Gaston Martin (2014)
Lately, researchers around the world have developed effective chemical and physical treatments on plant fibers to improve their compatibility with polymeric matrices. In addition, the need of high performance fabrics produced from plant fibers has been addressed by many manufacturers of textile reinforcements. These facts have increased the use of natural fibers in the composite industry. Liquid composite molding (LCM) techniques are suitable for mass production of high-quality composite parts. Basically, the reinforcement is compressed inside a mold and a thermosetting resin is injected to impregnate the fibers and fill the empty spaces in the mold. After the resin cures, the composite part is demolded. However, the processing of plant fiber–reinforced composites by the traditional techniques is not trivial, because the structure of plant fibers is more complex than that of synthetic fibers and due to their chemical composition rich in cellulose and hemicellulose, they are highly hydrophilic. This work presents a review on the main issues that arise during the processing of plant fiber reinforced composites by traditional liquid composite molding techniques.